Investigation on Single Ion Dynamics of Molten Alkali Chlorides by Molecular Dynamics Simulations - Wang, Jia; Lu, Guimin; Yu, Jianguo (Asian Journal of Chemistry, 2016)
Single ion dynamics of the two ionic species in each molten alkali chlorides at 1100 K have been studied with the molecular dynamics method through velocity auto-correlation functions. The self-diffusion coefficients of these ions have also been calculated from the time integral of the corresponding ionic velocity auto-correlation functions, which are in good agreement with the experimental values. For molten alkali chlorides, the ionic mass significantly affects the ionic dynamics. The self-diffusion coefficients of the light ions are larger than those of the heavy ones. In addition to the self-diffusion coefficients, velocity auto-correlation functions can provide a more intuitive description for the single-ion dynamics. For each melt, the velocity auto-correlation function of the light ions decays faster and exhibits a much more pronounced back scattering than its heavier partner. The velocity auto-correlation function of the light ions will be oscillatory if the mass difference of the two ionic species is significant. The oscillatory amplitude also increases as the mass difference increases.